A 35-year daily global solar radiation dataset reconstruction at the Great Wall Station, Antarctica: First results and comparison with ERA5, CRA40 reanalysis, and ICDR (AVHRR) satellite products - Zeng, Zhaoliang; Wang, Xin; Wang, Zemin; Zhang, Wenqian; Zhang, Dongqi; Zhu, Kongju; Mai, Xiaoping; Cheng, Wei; Ding, Minghu (Frontiers in Earth Science, 2022)
Solar radiation drives many geophysical and biological processes in Antarctica, such as sea ice melting, ice sheet mass balance, and photosynthetic processes of phytoplankton in the polar marine environment. Although reanalysis and satellite products can provide important insight into the global scale of solar radiation in a seamless way, the radiation observed in situ on the polar region remains poorly understood due to the harsh Antarctic environment. The present study attempts to employ empirical formulas and machine learning method to establish a 35-year daily global solar radiation (DGSR) dataset at the Great Wall Station, Antarctica using meteorological observation data during 1986-2020, which is then compared against the DGSR derived from ERA5, CRA40 reanalysis, and ICDR (AVHRR) satellite product. For the DGSR historical estimation performance, the machine learning method outperforms the empirical formula method overall. Among them, Mutli2 model (hindcast test R2, RMSE and MAE are 0.911, 1.917 MJ/m2, and 1.237 MJ/m2, respectively) for the empirical formula model and XGBoost model (hindcast test R2, RMSE and MAE are 0.938, 1.617 MJ/m2, and 1.030 MJ/m2, respectively) for the machine learning model were found with the highest accuracy. For the austral summer half-year, the estimated DGSR agrees very well with the observed DGSR, with a mean bias of only -0.47 MJ/m2. However, other monthly DGSR products differ significantly from observations, with mean bias of 1.05 MJ/m2, 3.27 MJ/m2 and 6.90 MJ/m2 for ICDR (AVHRR) satellite, ERA5 and CRA40 reanalysis products, respectively. In addition, The DGSR of the Great Wall Station, Antarctica followed a statistically significant increasing trend at rate of 0.14 MJ/m2/decade over the past 35 years. To our best knowledge, the Antarctica Great Wall Station daily global solar radiation spanning 1986–2020 was first reconstructed in this study, which is available upon request, will contribute to the surface radiation balance in Antarctica Peninsula.